The Alteration of Tomato Chloroplast Vesiculation Positively Affects Whole-Plant Source–Sink Relations and Fruit Metabolism under Stress Conditions. (26th September 2022) - Ahouvi, Yoav; Haber, Zechariah; Zach, Yair Yehoshua; Rosental, Leah; Toubiana, David; Sharma, Davinder; Alseekh, Saleh; Tajima, Hiromi; Fernie, Alisdair R; Brotman, Yariv; Blumwald, Eduardo; Sade, Nir
Abstract: Changes in climate conditions can negatively affect the productivity of crop plants. They can induce chloroplast degradation (senescence), which leads to decreased source capacity, as well as decreased whole-plant carbon/nitrogen assimilation and allocation. The importance, contribution and mechanisms of action regulating source-tissue capacity under stress conditions in tomato ( Solanum lycopersicum ) are not well understood. We hypothesized that delaying chloroplast degradation by altering the activity of the tomato chloroplast vesiculation (CV) under stress would lead to more efficient use of carbon and nitrogen and to higher yields. Tomato CV is upregulated under stress conditions. Specific induction of CV in leaves at the fruit development stage resulted in stress-induced senescence and negatively affected fruit yield, without any positive effects on fruit quality. Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9 (CRISPR/CAS9) knockout CV plants, generated using a near-isogenic tomato line with enhanced sink capacity, exhibited stress tolerance at both the vegetative and the reproductive stages, leading to enhanced fruit quantity, quality and harvest index. Detailed metabolic and transcriptomic network analysis of sink tissue revealed that the l -glutamine and l -arginine biosynthesis pathways are associated with stress-response conditions and also identified putative novel genes involved in tomato fruit quality under stress. Our results are the first to demonstrate the feasibility of delayed stress-induced senescence as a stress-tolerance trait in a fleshy fruit crop, to highlight the involvement of the CV pathway in the regulation of source strength under stress and to identify genes and metabolic pathways involved in increased tomato sink capacity under stress conditions.